FAKTOR KESULITAN BELAJAR MENULIS HURUF HIRAGANA PADA SISWA KELAS X SMA LABSCHOOL SURABAYA TAHUN AJARAN 2019/2020 - OLIVIA EKA MULYANA, TASMANIA (HIKARI, 2020)
Japanese learning that has been given to Labschool high school students in the city of Surabaya, does not match the desired target. Especially in the material hiragana letters. The learning objectives desired by the teacher are students able to write hiragana letters according to the rules, memorize hiragana, and can distinguish hiragana letters that look similar. When the teacher asks students to write hiragana letters on the board one by one with the aim of practicing the students competence in writing hiragana letters, there are several difficulties that are experienced. Such as the lack of graffiti on hiragana letters, cannot distinguish hiragana letters that look similar and scribbles that are not in order. The purpose of this study was to determine the difficulty factors facing students. This research is a type of descriptive research with survey method. The survey was conducted by distributing questionnaires in the form of a questionnaire to Labschool high school students in the city of Surabaya and processed into data. The population includes Labschool High School students who are studying Japanese, while the sample is first class Labschool High School students in the city of Surabaya. While the research data generated in the form of the results of respondents answers to the questions that have been given by researchers through questionnaires to obtain data about the factors of writing hiragana letters. The results of the study show the difficulty in learning to write hiragana letters derived from: 1. Do not memorize the sequence of writing hiragana, students still experience errors in writing hiragana letters, for example it is still difficult to distinguish the sequence in writing letters (a) and letters ? (o). 2. Difficulty reading hiragana letters, many students are enthusiastic about paying attention to the teacher when explained hiragana letters material. however there are still many students who still have difficulty when they try to write hiragana letters because the inability to read letters is automatically difficult to pronounce. 3. Difficult in remembering hiragana letters, students have difficulty memorizing hiragana letters, because hiragana letters are considered complicated, many letters are considered similar and are not accustomed to writing hiragana letters. 4. Cannot differentiate similar hiragana letters, students still cannot distinguish hiragana letters ? [a] and ? [o]. Keywords: Learning Difficulties, Writing Difficulty Factor, Hiragana Writing Difficulty Factor ?? ?????Labschool????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? ????????????????????????? ?????????????????????????????????????????? ???????????????Labschool??????IPA??IPS???????????? ?????????????????????????????????????????????????????????????? ????????????????????????? ??????????????????????????????????????????????a?? ??o?????????????????????????? ?????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? ????????????????????????????????????????????????????????????? ????????????????????????????[?]?[?]?????????????[?]?[?]?????????????????? ??????????????????????????????????